A identidade, o costume e o direito da decisão: um estudo sobre o uso e o desuso do sobrenome do marido - Giacometti, Fabiana Aparecida Prenhaca [UNESP] (2015)
The woman's right to choose between adding or not the husband's surname was promulgated in 1977. The surname of a person demarcates its identity, it is a right related to human decency. Therefore, the full name is the individualization of the human in the society, being one of the main rights of citizenship. Intangible element, but as fundamental as the set of goods and wealth held by individuals. For a long time for brides, it was a requirement: every woman that formalize her marriage, should add the husband's surname to her family. Today it became a choice and no more an obligation. This qualitative-descriptive research aimed to establish if in the practice the transformation in legislation changed the women habits in add or not the husband surname when marrying. From a questionnaire applied in 20 women who were married legally after the date of the right valance answered questions consisting of open and closed questions based on a guide for programmatic content analysis. The results obtained indicate that for most participants using the surname of her husband it happened in automatic mode (since their grandmothers and mothers carry the surname of their spouses), showing the strength of custom and exclusion toward the male, confirmed through the submission in do it without realizing why. Also discovered that not always the participants of this investigation were informed at City Hall about the possibility of not add the surname's husband to his name. Were not advised of their rights, lacking this education at school and in the family. With this clear lack of knowledge of the Brazilian Civil Code, brings the necessity of do a social work: this research culminates with a proposal of educational intervention that offers the cultural capital missed for the betrothed, because it is necessary to put people knowing the laws and their rights. The intervention is about a drafting of a booklet entitled ...